Fundamental issues in defense training and simulation - Best, Christopher. (Human factors in defence, 2013)
"Defence forces have always invested a great deal of their resources in training. In recent times, changes in the complexity and intensity of operations have re-affirmed the importance of ensuring that warfighters are adequately prepared for the environments in which they are required to work. The emergence of new operational drivers such as asymmetric threats, urban operations, joint and coalition operations, and the widespread use of military communications and information technology networks has highlighted the importance of providing warfighters with the competencies required to act in a coordinated, adaptable fashion, and to make effective decisions in environments characterised by large amounts of sometimes ambiguous information. While investment in new technologies can make available new opportunities for action, it is only through effective training that personnel can be made ready to apply their tools in the most decisive and discriminating fashion - and by doing so transform military technology into defence capability"-Provided by publisher.